Nanotechnology applications in the food industry. A Review - Gomes, Rafaela Cardoso [UNESP]; Abib Pastore, Victor Alessandro [UNESP]; Martins, Otavio Augusto [UNESP]; Biondi, Germano Francisco [UNESP] (Univ Federal Ceara, Centro Ciencias Agrarias, 2015)
The idea that the matter is composed of atoms exists about two thousand years ago, but only recently the nano prefix, writen with some other word, is becoming increasingly common use in the daily life of the population. Nanotechnology is a generic term for a set of technologies, techniques and procedures for further preparation, characterization, manipulation of atoms or molecules to build a new material in the nanometer scale. The recognition of nanoscience and nanotechnology is seen as a current trend in science and technology of the century, even though initially viewed as science fiction. Among the many areas that can benefit, the food industry is in fact one of the sectors that attracts more investments. This type of market includes the development of new functional materials, products, packaging, and methods for improving food safety. Nanosensors have been developed and used as potential alternatives for reducing the load of standard methods, for having quickly response time and, moreover, they are highly sensitive, robust and easy to use. The production of nanoparticles and nanostructured materials in an industrial scale can brings unpredictable consequences when compared to traditional methods. Nanomaterials can present many heavy metals in their composition that are toxic. In addition, due their small size, these compounds interact largely with both external and physiological environment. Thus, further studies related to the toxicity of these new materials are needed, both for the environment and for human health.
Keywords: nano; nanomaterials; food